DNA binding specificity of two homeodomain proteins in vitro and in Drosophila embryos. - Walter, J (1996)
In previous experiments, the homeodomain proteins even-skipped and fushi-tarazu were found to UV cross-link to a surprisingly wide array of DNA sites in living Drosophila embryos. We now show that UV cross-linking gives a highly accurate measure of DNA binding by these proteins. In addition, the binding of even-skipped and fushi-tarazu proteins has been measured in vitro to the same DNA fragments that were examined in vivo. This analysis shows that these proteins have broad DNA recognition properties in vitro that are likely to be important determinants of their distribution on DNA in vivo, but it also shows that in vitro DNA binding specificity alone is not sufficient to explain the distribution of these proteins in embryos.